Development of Nursing Manpower Management Model for Patient Safety: a Pilot Study in Ratchaburi Province - Sathira-Angkura, Teeraporn; Jamsomboon, Kanogporn; Wongsuvansiri, Somchit; Leelawong, Sirima; Boonkaew, Hatairut (Journal of Health Science of Thailand, 2019)
The objective of this action research was to develop and study the outcomes of a nursing manpower management model for patient safety in the 11 hospitals under the Ministry of Public Health in Ratchaburi province. The research involved 122 research participants from the nurse administrators of the target hospitals, 11 head nurses, and 320 randomly assigned nurses who were the sample group. It was conducted in 3 phases: situation analysis, model development and implementation, and model evaluation. Quantitative and qualitative data were collected by using mixed methods. The instruments used consisted of two parts (1) the research instrument which was guidelines of nursing manpower management for patient safety, and (2) the data collection instruments comprising of a survey form and discussion guidelines for the situation analysis and for the evaluation of the model, the model results recording form, and the questionnaire as well as the evaluation form of the model with Cronbach’s alpha coefficient of 0.95 and 0.96, respectively. Each instrument was checked for content validity. The data were analyzed by using descriptive statistics and content analysis. It was found that the model comprised of the roles of head nurses, nursing manpower management policy, nursing manpower management committee, and the guidelines of nursing manpower management for patient safety which consisted of four strategies, namely nursing manpower management under Thailand nursing and midwifery council declaration, nursing task review, skill mix, and lean management. The results after implementation revealed that the nurses’ opinion to the model was at a high level. The nurse administrators agreed that the model was appropriate. Most of hospitals (90.9%) showed that the results of 5 patient indicators and the results of 2 nursing management indicators for patient safety were improved. Average of nurses work hours reduced from 63.8 to 55.5 hours per week.